Development and test of hydraulic driven remote transporter - Li, Jiaxue; Li, Shanjun; Zhang, Yanlin; Liu, Mingdi; Gao, Zhiyuan (International Journal of Agricultural and Biological Engineering, 2021)
To solve the problems of the traditional orchard conveyor, such as inflexible steering, a complex structure, poor stability and no power grid coverage, a remote-controlled rail conveyor powered by hydraulic pressure for mountainous orchards was designed and manufactured. Climbing stress analysis was carried out on a full-load trailer to obtain the maximum traction force, which meets the requirement of the climbing slope of the transport mechanism. The key components of the conveyor were developed, such as the hydraulic transmission, the control system, safety protection devices, limiting devices, the throttle and decompression actuator, the counterweight tension and the battery. Through the theoretical calculations of key components, an orchard conveyor powered by diesel and hydraulic pressure was designed. Finally, the working performance of the transporter was tested through functionality, driving speed, system pressure and remote-controlled tests. The test results showed that the climbing angle of the transporter can reach 50°, the uphill load can reach 840 kg, the downhill load can reach 1100 kg, and the average running speed is 0.77 m/s; the driving speed ranges from 0.29 m/s to 1.08 m/s, and the system pressure ranges from 3.2 MPa to 10 MPa. The driving speed and system pressure are significantly affected by the load, and the remote control distance can reach 455 m. The technical specifications of the transporter meet all the design requirements, and the problem of stable operation of the transporter without power grid coverage has been addressed. The research results can well meet the practical application requirements of mountain orchard transportation without power grid coverage and provide theoretical reference for the design of key components of mountain orchard transportation machinery. Keywords: mountain orchard, conveyor, hydraulic drive, remote control DOI: 10.25165/j.ijabe.20211402.5844 Citation: Li J X, Li S J, Zhang Y L, Liu M D, Gao Z Y. Development and test of hydraulic driven remote transporter. Int J Agric & Biol Eng, 2021; 14(2): 72–80.